Application of grey-fuzzy logic for the optimization of process parameters on CNC turning of EN8-steel - Acharya, A. K.; Thatoi, D. N.; Routara, B. C. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.